2021
DOI: 10.33448/rsd-v10i6.15713
|View full text |Cite
|
Sign up to set email alerts
|

Plantas com potencial medicinal em quintais agroflorestais: diversidade entre comunidades rurais do Portal da Amazônia - Mato Grosso, Brasil

Abstract: Os quintais caracterizam opções de uso da terra para conciliar a produção agrícola e florestal, simultaneamente à conservação dos recursos naturais. Este presente trabalho objetivou caracterizar e identificar as espécies vegetais com potencial medicinal em 44 quintais, implantados e manejados por agricultores familiares, em comunidades rurais nos municípios de Alta Floresta (AF) e Nova Canaã do Norte (NCN), no Portal da Amazônia (MT). Foram feitas visitas guiadas durante o mês de agosto de 2017, a fim de mapea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…Diagnosis with more than 500 families of farmers in the Santarém plateau showed that 70% of farmers had expanded their crops with a focus on fruit production [74]. This pattern was also observed in the evaluation of home gardens in several places in the country [75] and in studies in home gardens in Amazonia [25,76,77], where fruit-bearing trees such as açaí, cupuaçu, and banana are the more frequent species. Among the ten most frequent species (34.5 to 54.6%), exotic species are predominant.…”
Section: Featured Species In Homegardensmentioning
confidence: 60%
“…Diagnosis with more than 500 families of farmers in the Santarém plateau showed that 70% of farmers had expanded their crops with a focus on fruit production [74]. This pattern was also observed in the evaluation of home gardens in several places in the country [75] and in studies in home gardens in Amazonia [25,76,77], where fruit-bearing trees such as açaí, cupuaçu, and banana are the more frequent species. Among the ten most frequent species (34.5 to 54.6%), exotic species are predominant.…”
Section: Featured Species In Homegardensmentioning
confidence: 60%
“…Os QAFs, também, podem ser considerados fonte de recursos medicinais, onde são cultivadas diferentes espécies de plantas com propriedades terapêuticas conhecidas a partir de saberes e práticas populares, como recurso primário para o tratamento de várias enfermidades das populações humanas (Pereira et al, 2021).…”
Section: Introductionunclassified